(untitled) - Soloman, Sabrie (New York, 1994)
This book offers step-by-step guidance on applying sensors to measure product parameters, control manufacturing operations, implement flexible manufacturing systems (FMS) and computer-integrated manufacturing (CIM), development precision manufacturing systems, and generate and control motion. It also includes information on the latest technological breakthroughs made by NASA and other U.S. research institutes
Keywords: Automatic data collection systems,Detectore,Process control; Automation